Physical education social attitudes and leadership qualities - Satyanaryana, V. (New Delhi : Discovery Publishing House)
tudy undertaken in schools, colleges, play fields of district sport centres of various towns, chiefly from Andhra Pradesh, India.
Includes index.
Keywords: Physical education and training -- Social aspects